Masyarakat Hukum Adat dan Hak Ulayat di Provinsi Papua Barat Sebagai Orang Asli Papua Ditinjau Dari Sisi Adat dan Budaya: Sebuah Kajian Etnografi Kekinian - Andreas Jefri Deda; Suriel Semuel Mofu (Jurnal Administrasi Publik, 2014)
This ethnographic paper discusses cultural tranformation of the indigenous people of Papua in their land. Specifically the paper presents a study on the change of tribal right among the indigenous people of Papua in the West Papua province. Indigenous Papuan people in the West Papua province are traditionally recognized as part of the Bomberay dan the Doberay culture. The indigenous people of Papua who are living in this area are linguistically very complex because the balanced distribution of Austronesian a language and Papuan language in the area, and it has created transformation of language grammar among the Papuan group of people. Culturally, there are two leadership systems practiced in the area namely the kingdom leadership system and the mix leadership system. In performing rights of land, they commonly share the same philosophical beliefe; the „religio – magis‟ relationship. In ethnographical condition, those original cultural practices are objects of transformation. Linguistically, today‟s majority of the indigenous people are shifting from their mother tongue as their first language (L1`) into bahasa Indonesia (Malay) as the second language (L2). In the leadership system, they are mostly practicing the head of the tribe system, not the original one. In the performing rights toward land as landlords, they seem to have no sacred „religio - magis‟ relationship with the land.